In Vivo Scanning Laser Confocal Microscopy of Conjunctival Goblet Cells in Medically-controlled Glaucoma - DI STASO, SILVIO (In Vivo, 2018)
Aim: The aim of this study was to evaluate the goblet cell density (GCD) of conjunctiva in medically-controlled glaucoma using laser scanning confocal microscopy (LSCM). Materials and Methods: Fifty-five glaucomatous patients were enrolled and divided into two groups: Group 1 (27 eyes), controlled with one medication; and group 2 (28 eyes), controlled with two medications. Seventeen patients with dry eye disease (DED) and 17 healthy individuals served as controls. Patients completed the Ocular Surface Disease Index (OSDI) questionnaire and underwent determination of tear film break-up time (BUT), corneal staining, and Schirmer test I. For the GCD assessment, 12 high-quality images were acquired from the upper conjunctival epithelium (superior nasal, superior central, and superior temporal sectors). Results: Overall, GCD was significantly reduced in both glaucoma groups and those with DED compared to healthy controls (p<0.001), with values markedly lower in group 2 compared to group 1 (p<0.05). GCD was not significantly different between those with DED and group 2. A significant negative correlation was found of GCD with OSDI and with BUT (p<0.001; R=–0.795 and R=–0.756, respectively). Conclusion: Glaucoma therapy leads to a marked reduction of GCs, especially in the associative regimens. Given the negative correlation with tear film function tests, GCD reduction may play a pivotal role in the pathophysiology of the glaucoma-related disease of the ocular surface